2014
DOI: 10.1177/082585971403000102
|View full text |Cite
|
Sign up to set email alerts
|

Looking beyond Disfigurement: The experience of Patients with Head and Neck Cancer

Abstract: Despite the frequent occurrence of head and neck cancer (HNC) disfigurement, little is known about its psychosocial impact on patients. This study aimed to understand the lived experience of disfigurement in HNC and explore what patients considered to be its influences. Fourteen disfigured HNC patients participated in a 45-to-120-minute in-depth, semi-structured interview, which was analyzed qualitatively using interpretive phenomenology. A majority of participants (64 percent) were considered to be at an adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 28 publications
5
71
0
Order By: Relevance
“…During the diagnosis and treatment period, the way in which the care team dealt with the changed facial appearance was important (Henry et al, 2014;Konradsen et al, 2009;Lee et al, 2016;Speraw, 2009 Participants' descriptions suggest a balance is needed between acknowledging appearance changes without stigmatizing. Konradsen et al (2009) found that appearance was minimized by the care team, meaning that the participant's negative feelings about their appearance were silenced as they learned that altered appearance, whilst an important issue to them, was not something that was of importance to staff.…”
Section: The Care Teammentioning
confidence: 99%
See 4 more Smart Citations
“…During the diagnosis and treatment period, the way in which the care team dealt with the changed facial appearance was important (Henry et al, 2014;Konradsen et al, 2009;Lee et al, 2016;Speraw, 2009 Participants' descriptions suggest a balance is needed between acknowledging appearance changes without stigmatizing. Konradsen et al (2009) found that appearance was minimized by the care team, meaning that the participant's negative feelings about their appearance were silenced as they learned that altered appearance, whilst an important issue to them, was not something that was of importance to staff.…”
Section: The Care Teammentioning
confidence: 99%
“…Negative reactions from others in response to changed facial appearance were a significant theme in the majority of studies (Bonanno, & Choi, 2010;Bonanno, & Esmaeli, 2012;Costa et al, 2014;Henry et al, 2014;Konradsen et al, 2012;Speraw, 2009;Turpin et al, 2009;Van Doorne et al, 1994). These included those of commission (e.g.…”
Section: Others' Negative Reactionsmentioning
confidence: 99%
See 3 more Smart Citations